Human herpesvirus 8-associated multicentric Castleman disease in a patient with advanced HIV infection: A case report - Theerajet Guayboon (2022)
Rational:Multicentric Castleman disease (MCD) is a nonclonal lymphoproliferative disorder that is rarely reported from Southeast Asian countries. Here, we report a case of human herpesvirus 8 (HHV-8)-associated MCD in a patient with advanced human immunodeficiency virus (HIV) infection who presented with prolonged intermittent fever, urticarial rash, hepatosplenomegaly, and generalized lymphadenopathy.Patient concerns:A 34-year-old man with advanced HIV infection who was in good compliance with his antiretroviral treatment regimen presented with intermittent fever, weight loss, marked hepatosplenomegaly, and generalized lymphadenopathy. Recurrent symptoms of high-grade fever, abdominal discomfort, pancytopenia, and high C-reactive protein level occurred for 16 months.Diagnoses:Histopathological findings of left inguinal lymph node revealed diffuse effacement of lymph node architecture with coexpression of HHV-8 latency-associated nuclear antigen 1 from immunohistochemical staining. The HHV-8 viral load was 335,391 copies/mL.Interventions:The patient was treated initially with one dose of intravenous rituximab (375 mg/m2) followed by subcutaneous rituximab (1400 mg) weekly for 5 weeks.Outcomes:The patient's recurrent systemic symptoms subsided dramatically, and he has now been in remission for almost two years.Lessons:HHV8-associated MCD remains a diagnostic challenge in advanced HIV disease and should be suspected in those with recurrent flares of systemic inflammatory symptoms. Lymph node histopathology is essential for diagnosis and for excluding clonal malignancy. HHV-8 viral load is also useful for diagnosis and for monitoring disease activity.